2016
DOI: 10.1103/physrevb.94.235407
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic order induced on graphene by Ni/Co proximity effects

Abstract: We build a tight-binding Hamiltonian describing Co/Ni over graphene, contemplating ATOP (a Co/Ni atom on top of each Carbon atom of one graphene sublattice) and HCP (one Co/Ni atom per Graphene plaquette) configurations. For the ATOP configuration the orbitals involved, for the Co/Ni, are the d z 2 −r 2 which most strongly couples to one graphene sublattice and the dxz, dyz orbitals that couple directly to the second sublattice site. Such configuration is diagonal in pseudospin and spin space, yielding electro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…The effective overlaps are a result of the presence of the atomic spin-orbit coupling, using the Slater-Koster formulation [27,28] and a lowest-order matrix perturbation theory as proposed in ref. [29]. The effective SO coupling obtained recovers that of ref.…”
Section: Analytical Slater-koster Model For Double-stranded Dnasupporting
confidence: 81%
See 2 more Smart Citations
“…The effective overlaps are a result of the presence of the atomic spin-orbit coupling, using the Slater-Koster formulation [27,28] and a lowest-order matrix perturbation theory as proposed in ref. [29]. The effective SO coupling obtained recovers that of ref.…”
Section: Analytical Slater-koster Model For Double-stranded Dnasupporting
confidence: 81%
“…Here we derive the effective Hamiltonian of the DNA incorporating spin coupling from the more compact approach of band folding. [29,33] We consider an intrinsic atomic SO coupling (associated to C or N for the DNA bases) given by…”
Section: Analytical Slater-koster Model For Double-stranded Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic configuration, which is initiated by the magnetic interaction of of graphene, since the previous studies have only reported that the induced magnetic moment of graphene is either in the AFM configuration [31] or FM configuration [32]. An additional remarkable point is that the total energy difference between the anti-parallel and parallel configurations is in the order of meV, which implies that the magnetic configuration change does not require an extremely high external magnetic field.…”
Section: Total Energy and Magnetic Propertiesmentioning
confidence: 98%
“…Graphene/transition metal interfaces have been recognized as a very attractive hybrid systems [1][2][3][4][5] since its proximity may lend fascinating properties that the otherwise isolated graphene layer lacks. Namely, the gate controlled dopability [6], the transfer of ferro and antiferromagnetism [1,7], and the induced strong spin-orbit coupling [8], just to mention a few. In addition, more complex transition metal substrates such as transition metal dichalcogenides on few-layer graphene hybrid spin-valves have shown to induce opto-valley spin-injection due to its large SO coupling [9,10].…”
Section: Introductionmentioning
confidence: 99%